Leading Learning Networks in Education - Lazarová, Bohumíra; Pol, Milan; Lelieur, Ruud; Schelfhout, Wouter; Vanhoof, Jan; Vanlommel, Kristin; Brejc, Mateja; Erčulj, Justina; Hortlund, Torbjörn; Malmberg, Kristina; Devlin, Linda; Morgan-Guthrie, Rachel; et al. (Masaryk University Press, 2022)
This study is one of the main outcomes of Leading Learning by Networking, an Erasmus+ project. It concerns the management of learning networks in schools with regard to the mission of these networks in the context of growing diversity. The text consists of three main parts. The opening chapter is of theoretical study, dealing with the term Professional learning networks and various factors that facilitate this form of collaboration in schools. Attention is also paid to the role of headteachers in the creation of and support for learning networks. The second part is a summary of the results of a qualitative research, which was carried out by means of interviews, aimed at recognition of some aspects of networking in selected schools in the partner countries. Part three describes a range of data obtained from a questionnaire survey on headteachers’ needs and experience in the management of learning networks.